Islam, Agrarian Struggle, and Natural Resources: The Exertion of Front Nahdliyin for Sovereignty of Natural Resources Struggle Towards Socio-Ecological Crisis in Indonesia - Abdul - Kodir; In’amul Mushoffa (Institut Agama Islam Negeri Madura, 2017)
Indonesia is currently embroiled in social and ecological crisis as a result of the exploitation of natural resources redundant as a consequence of the dominance of the global capitalist system. As a country with a Muslim majority deemed the need for religious organizations to resolve the issue. In 2013, Front Nahdliyin for Sovereignty of Natural Resources (FN-KSDA) was established as a response to the social-ecological crisis in Indonesia. Among NU members (Nahdliyin), the existence of organizations such as FN-KSDA is something new. In the middle of NU's attention to the agrarian conflict and natural resources that are considered quite minimal, until now FN-KSDA moving outside the formal structure of the NU. This study also examines how the perspective of FN-KSDA against the sovereignty of natural resources. This article reviews the importance of the agrarian reform carried FN-KSDA by relying on sources of Islamic law that the Qur'an and Hadith, as well as the results of the NU congress. The agrarian reform and upholding the sovereignty of natural resources made FN-KSDA are already have a legitimacy whether from the main sources of Islamic law, the Qoran and the hadith as well as internal decisions of organizations such as Nahdlatul Ulama.Copyright (c) 2017 by KARSA. All right reserved DOI: 10.19105/karsa.v25i1.1160